Performance of biochar-based filtration bed for the removal of Cr(VI) from pre-treated synthetic tannery wastewater. Issue 2 (15th January 2021) - Deepa, Arukula; Prakash, Prem; Mishra, Brijesh Kumar
ABSTRACT: In the present study, the performance of biochar-based filtration bed was assessed to enhance the removal efficiency of Cr(VI), from the pre-treated synthetic tannery wastewater. The pre-treatment of wastewater was carried out with aluminium formate (AF) as a coagulant and 80% Cr(VI) removal was observed which might be due to the formation of carboxylic complexation reaction. The purity of coagulant and the sludge components were validated with XRD analysis and the results revealed the formation of pure aluminium formate compound as well as a clear change in the crystalline structure in the treated sludge. FT-IR spectra demonstrated the carboxylic compound participated in the removal of Cr(VI) during the coagulation process. The pre-treated wastewater having 20 mg/L (residual) Cr(VI) was passed through a three-layered filtration bed containing biochar, which showed complete removal of Cr(VI) ∼ 99.99% by precipitating into bind form under the influence of CaCO3 and formate ions. The possible mechanistic approach might be due to the presence of formate ions in the pre-treated wastewater, the precipitation of Cr(VI) occurred in the form of Cr(OH)2 by the release of bicarbonate (HCO 3− ), carbonate ion (CO3 2− ) and hydroxide (OH − ) ions in the filtration bed. The properties of the biochar were investigated by XRD and FTIR analysis and the results revealed the existence of hydroxyl, carboxyl and carbonyl groups, which participated during the removal of Cr(VI). The results suggest that biochar-based filtration bed could be a promising method for the treatment of pre-treated tannery wastewater. GRAPHICAL ABSTRACT: UF0001